Compliance with Taking Hypertension Medication in the Elderly at Kebun Handil Health Center, Jambi City in 2024 - Ramadani, Latifa Fitri Ramadani; Butar, Marta Butar; Wisudariani, Evy; Syukri, Muhammad; Fitri, Adelina (PT FORMOSA CENDEKIA GLOBAL, 2024)
Treatment of hypertension can be done through a healthy lifestyle and the use of antihypertensive drugs. The use of antihypertensive drugs alone has proven to be insufficient in controlling blood pressure in the long term effectively. Compliance with drug consumption is also a very important factor. This type of finding is quantitative through a cross sectional design. The sample selection technique uses simple random sampling. Data was collected through questionnaires, then univariate and bi-variate data analysis using the chi-square test. The frequency distribution of medication adherence levels by hypertensive patients at Kebun Handil Community Health Center, Jambi City, highlights the existence of significant problems in medication adherence among the population studied. The analysis shows that not all demographic and environmental factors have a significant relationship to the level of adherence to taking hypertension medication.